Treatments for objective and subjective cognitive functioning in young people with depression: Systematic review of current evidence. Issue 10 (25th November 2021) - Daglas‐Georgiou, Rothanthi; Bryce, Shayden; Smith, Gabriel; Kaur, Manreena; Cheng, Nicholas; De Rozario, Magdalene; Wood, Stephen J.; Allott, Kelly
Abstract: Aim: Cognitive deficits are recognized features of depressive disorders in youth aged 12–25. These deficits are distressing, predict functional impairment and limit the effectiveness of psychological therapies. Cognitive enhancement using behavioural, biochemical or physical treatments may be useful in young people with depression, but studies have not been synthesized. The aim was to systematically review the evidence for treatments for objective and subjective cognitive functioning, and their acceptability and functional outcomes in people aged 12–25 with depression. Method: Three electronic databases were searched for articles using pre‐specified criteria. Pharmacological treatments were not eligible. Risk of bias was rated using the Cochrane Collaboration's revised risk‐of‐bias tool. Dual full‐text article screening, data extraction and quality ratings were completed. Results: Twelve studies were included for review (median participant age: 20.39 years), five of which were randomized‐controlled trials (RCTs). Sample sizes were generally small (median = 23; range: 9–46). Eight studies investigated behavioural treatments including aerobic exercise, cognitive training and education or strategy‐based methods. Four studies examined repetitive transcranial magnetic brain stimulation (rTMS). Most behavioural treatments revealed preliminary evidence of improved cognitive function in youth depression. Consent rates were greatest for exercise‐ and education‐based approaches, which may indicate higher acceptability levels. Findings from rTMS trials were mixed, with only half showing cognitive improvement. Functional outcomes were reported by three behavioural treatment trials and one rTMS trial, with functional improvement reported only in the former. Some concern of risk of bias was found in each RCT. Conclusion: Behavioural treatments, such as exercise, cognitive training and education/strategy‐focused techniques, show encouraging results and appear to be acceptable methods of addressing cognitive deficits in youth depression based on participation rates. Brain stimulation and biochemical treatments (e.g., nutrient‐based treatment) require further investigation.